Evolution of Major Amputation Risk in Patients Hospitalized in France for Critical Limb Ischemia: The COPART Registry. (April 2021) - Coudene, Alice; Lapébie, Francois-Xavier; Desormais, Ileana; Lacroix, P.; Aurillac, Valerie; Mangin, Marion; Aboyans, V.; Bura-Rivière, Alessandra; Messas, Emmanuel; Constans, Joel; Boulon, Carine
Over the past decade, improvements in medical treatment and revascularization techniques have been beneficial for patients with peripheral artery disease in the late stage of critical limb ischemia (CLI). We evaluated the putative reduction in the number of major amputees in the Cohorte des Patients ARTeriopathes (COPART) cohort over time. Patients were selected from this multicenter cohort, from 2006 to 2016, for CLI according to Trans-Atlantic Inter-Society Consensus for the Management of Peripheral Arterial Disease II criteria. Patients included before and after 2011 were compared. Patients were followed for 1 year. Primary outcome was the rate of major amputations. Secondary outcomes were minor amputations, deaths from all causes, cardiovascular deaths; 989 patients were included, 489 before 2011 and 450 after 2011. There was a significant decrease in rates of major amputation after 2011 (17% vs 25%), confirmed in multivariate analysis (odds ratio [OR]: 1.5 [1.1-2.2]), an increase in revascularization, particularly distal angioplasty (OR: 2.7 [1.7-4.4]) and increased statin intake (OR: 1.6 [1.1-2.1]). For secondary outcomes, there was no significant difference. Limb prognosis of CLI patients has improved over the past decade, possibly due to more revascularizations, particularly distal ones, and increased statin use.